Republic of Lebanon - Water sector : public expenditure review - World Bank (World Bank, 2012)
The state of the water supply and sanitation (WSS) sector in Lebanon is not in line with the level of economic development reached by the country. Despite the relatively high coverage rate in the water sector (78 percent), continuity of supply is extremely low. The Beirut Mount Lebanon (BML) region, which accounts for 60 percent of total connected households, receives only three hours of daily water supply during the summer season. The development of the wastewater sector is still at an embryonic stage. There are a few waste water treatment plants in operation, all of which are small. Water storage capacity is inadequate to meet irrigation water demand, and is far below the level of other MENA countries. The present public expenditure aims at examining efficiency and effectiveness in the allocation of resources in the water sector. In conducting the research and analysis, the team observed a contrasted reality in which a multitude of issues afflicting the sector emerged. Alongside the public expenditure analysis, the study presents an in-depth diagnosis of the water sector in Lebanon and the issues it is facing. The analysis focuses primarily on water supply, encompassing to a lesser extent sanitation and irrigation, due to the scarcer information available on the latter two sub-sectors. The public expenditure review addresses the following main questions: what progress has Lebanon made in reforming the water sector? What are the main weaknesses still characterizing its current institutional setting? Is the water sector performance in line with the level of economic development in the country? What are the key issues faced by consumers in the water sector? Has public expenditure been adequate to meet the development needs of the sector? What is the level of efficiency of public investment? What are the key sources of hidden costs in the water sector? What are the main accountability weaknesses which should be overcome to improve efficiency in the delivery of water supply and sanitation services in Lebanon? What policy actions are needed to improve sector performance and meet the development needs of the sector?